STUDY OF GEOTHERMAL STEAM PURITY IN GEOTHERMAL POWER PLANT - Wilantara, Bayu
Geothermal is a renewable energy source with great potential in Indonesia. The utilization is mostly used for electricity generation. However, there are obstacles faced, the content of geothermal vapor damage the turbines such as erosion and corrosion of turbine blades. The contents are minerals and total dissolved solid which is carried along with steam into the turbine. Therefore, it is necessary to study the vapor content of geothermal power plants starting from the wellhead, separator, scrubbing line, and scrubber. Steam content is calculated from the wellhead to turbine. In addition, the calculation of separator efficiency and condensate load on scrubbing line are also carried out. Next step is a simulation of steam content calculation on a geothermal power plant model. The data used refers to one of the geothermal power plants in Indonesia. It was found that the separator efficiency was 75.48%, using 1490 kPa well pressure, 2700 kJ/kg enthalpy, and 40.8kg/s flow rate of geothermal fluid (steam-brine mixture) at steam header. The steam fraction at separator inlet 95.63% and the steam fraction exits the separator 98.81%. The scrubbing line obtained condensate load of 0,081 kg/s with a reduction in moisture content of 1.18% and minerals and TDS reduced by 97.66%. The steam content in the turbine meets the predetermined standards, namely 0.0062% moisture content, 0.0026 ppm Cl, 0.00015 ppm SiO2, 0.00011 ppm B, 1.21x10-6 ppm Fe and 0.0052 ppm TDS. Using simulation data, 1200 kPa steam header pressure, 50 kg/s mass flow rate of geothermal fluid (steam-brine mixture) at steam header, and 1600 kJ/kg enthalpy obtained separator efficiency of 93.64% and steam fraction of 98.79%. The steam contents at the turbine inlet with simulation data are 0.37% moisture content, 0.0656 ppm Cl, 0.0039 ppm SiO2, 0.0028 ppm B, 3.67x10-5 ppm Fe, and 0.1312 ppm TDS.